Implementation of motion capture support in smartphones - Martinsson, Johannes; Trost, Reimund (My University, 2010)
This thesis investigates the feasibility of developing cross-platform smart phone applications that utilize the Qualisys motion capture system. An Application Programming Interface that implements an in-house communication protocol is created for use on smart phones and other portable devices. Furthermore, two iPhone applications that utilizes the API are implemented - a viewfinder and a goniometer. Denna rapport utreder möjligheterna att utveckla plattformsoberoende applikationer för smarta telefoner som utnyttjar Qualisys system för motion capture. Fokus är dock inriktat på utveckling för iPhone. Ett bibliotek för realtidskommunikation med Qualisys Track Manager beskrivs även. Slutligen presenteras två iPhone-applikationer som använder biblioteket - en sökare och en goniometer.
Keywords: Datorteknik; Computer Engineering